A 30-day-old Infant with Meningitides due to Invasive Methicillin-sensitive Staphylococcus aureus Infections: A Case Report - Ela Cem; Elif Kıymet; Elif Böncüoğlu; Şahika Şahinkaya; Miray Yılmaz Çelebi; Mine Düzgol; Aybüke Akaslan Kara (Galenos Publishing House, 2022)
One-month-old girl was referred to our hospital because of ongoing fever and methicillin-sensitive Staphylococcus aureus (S. aureus) (MSSA) positivity in blood cultures, despite the administration of antimicrobials for 14 days. Although there was, no immunodeficiency or underlying disease that could be a risk factor for infection, on the 14th day of the cefotaxime for MSSA meningitides, the persistence of leukocytosis in cerebrospinal fluid (CSF) analyses also was continued. After administration 30 days of treatment, the patient was discharged from the hospital with a normal CSF analysis and clinic. Central nervous system infections caused by S. aureus are uncommon in pediatric patients. The treatment of S. aureus meningitis is challenging because of the lack of established management guidelines, difficulty in achieving therapeutic drug concentrations in CSF, and presence of resistant strains. Therefore, it has a high clinical importance. This case is presented to emphasize that meningitis due to S. aureus difficulty in the treatment management, and need for further examination.